Description of Problem Solving Ability of Class X Students of Al-Azhar 10 Pontianak Islamic High School on Chemical Bonding Subject Material - Tri Indri Yani; Eny Enawati; Tulus Junanto; Rini Muharini; Rahmat Rasmawan (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This research was conducted to determine the problem solving ability of class X students of Al-Azhar 10 Pontianak Islamic High School on chemical bonding material. The type of research is descriptive qualitative problem solving ability. The research subjects were X IPA 1 class students of Al - Azhar 10 Pontianak Islamic High School totaling 21 people. Data collection tools include test questions designed based on problem-solving and interview guidelines developed based on problem-solving—data collection techniques using measurement techniques and direct communication techniques, namely written tests and unstructured interviews.The results of the problem solving ability data analysis were calculated using a problem solving ability assessment instrument and were presented as a whole based on the problem solving criteria instrument. The results of the analysis obtained students' problem solving ability on chemical bonding material, namely indicators of understanding the problem 49% (sufficient), making a plan 56% (sufficient), implementing a plan 63% (good), and checking back 70% (good) with an average percentage of 60% (sufficient). So it can be concluded that students' problem solving skills on chemical bonding material have an adequate predicate.